RANCANG BANGUN APLIKASI E-VOTING KETUA OSIS DI SMA PGRI 1 KOTA SERANG - Dadang Amiruddin; Irma Yunita Ruhiawati; Murnati Murnati (Jurnal Sistem Informasi dan Informatika (Simika), 2021)
The purpose of design is to develop an e-voting application for election of student council (OSIS) chairman in SMA PGRI 1 Kota Serang. The application will help optimize the process of selecting OSIS chairman through website-based e-voting so as to minimize the risk of errors in calculation of voting results due to human errors. The application design used Waterfall method so that it is easier to develop and use UML (Unified Modeling Language) for visual system modeling. This applicatio.n is developed using PHP programming language, MySQL database and CodeIgniter framework. The process of selecting OSIS chairman is carried out through the application by accessing the URL link and logging in with National Student ID Number (NISN) as the username and password, it will be given by OSIS coach at the time of election. Vote process by clicking the vote button, the number of voting votes that have been given will enter the voting results menu. If the student has already voted, the vote button will be hidden so that students cannot vote twice. This application also applies the Naïve Bayes algorithm to the e-voting application of OSIS chairman, using the probability formula, which is the number of students who choose candidates divided by all students per class. The voting results are obtained from the number of votes of voters who have voted. With the e-voting application, election of OSIS chairman becomes more effective and efficient than conventional or manual voting using paper.